Digital Criminalisation: The role of Electronic Evidence in the 17 + 8 Demonstration - Wijaya, Emilia Metta Karunia (Universitas Medan Area, 2025)
This article examines the role of electronic evidence and the practice of digital criminalisation in the series of demonstrations in response to 17+8 people's demands. The purpose of this study is to analyse the position of electronic evidence in proving criminal acts in the series of protests 17+8 of people's needs, the application of the ITE Law to the digital activities of the 17+8 demonstrations in the context of digital criminalisation, and the adequacy of legal norms in protecting freedom of expression in the digital era. The research uses a normative juridical method with a case study approach to examine the practice of digital criminalisation during a series of demonstrations. This study highlights an ambivalence in the use of electronic evidence. While it serves as a tool for accountability, it is also weaponized through the ITE Law's vague provisions to repress dissent. Consequently, Indonesia's legal framework remains focused on maintaining public order rather than safeguarding the fundamental rights of demonstrators. This article recommends reformulating the ITE Law's provisions on rubber articles, strengthening the implementation of the PDP Law, and establishing an independent institution to oversee the protection of personal data and digital restrictions.